2011
DOI: 10.1159/000327264
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Gastrointestinal Disorders in Infants: A Japanese Case Series

Abstract: Background: Eosinophilic gastrointestinal disorders (EGIDs) are disorders characterized by primary eosinophil inflammation in the gastrointestinal tract. There are a small number of reports of eosinophil infiltration in gastrointestinal tracts presenting as EGIDs in infants. In this study, we present Japanese cases of EGIDs in infants. Methods: Five patients diagnosed with or strongly suspected to have EGIDs in our hospital from 2008 to 2010 were reviewed. Radiographic contrast enema examinations and/or endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Many patients with EGE have been reported in Asian countries, with increasing numbers with EoE reported in Western countries [2,17,18]. We have previously reported that, in the routine endoscopic study, a EoE patient was found in approximately 0.02% of the endoscopy investigated Japanese cases [19].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with EGE have been reported in Asian countries, with increasing numbers with EoE reported in Western countries [2,17,18]. We have previously reported that, in the routine endoscopic study, a EoE patient was found in approximately 0.02% of the endoscopy investigated Japanese cases [19].…”
Section: Discussionmentioning
confidence: 99%
“…Interesting findings have been shown in patients with infantile food protein-induced allergic proctocolitis, which is basically synonymous with infantile eosinophilic colitis. The patients with food protein-induced allergic proctocolitis showed not only severe eosinophilic infiltration with degranulation, but also CLCs [ 104 ]. CLCs are generated when eosinophils fall into EETosis, which causes dysregulation of galectin-10, and this is associated with the severity of inflammation.…”
Section: Lessons From Eosinophilic Gastrointestinal Disordersmentioning
confidence: 99%
“…The development of food allergy in this group is largely related to the immaturity and permeability of the intestinal barrier [29]. Although the methods of food allergy diagnostics are constantly improving, the final diagnosis requires a test of elimination and provocation with the allergen with the subsequent clinical evaluation of the patient [30].…”
Section: Fibrosismentioning
confidence: 99%